Electrical Engineering RANCANG BANGUN HMI ATS DAN AMF BERBASIS PLC MODICON TM221CE24T - Fitra Rahmalia Rusli; Hendri Novia Syamsir (Politeknik Caltex Riau, 2021)
To regulate the change in the power supply from the main power source (PLN) to a backup power source (Genset) or vice versa, a control system that can work automatically is needed. The automatic control usually uses tools, namely Automatic Transfer Switch (ATS) and Automatic Mains Failure (AMF). PLC Modicon TM221CE24T with SoMachine Basic software in the form of ladder diagram programming language will control the work of this Automatic Transfer Switch and Automatic Mains Failure system. In addition, monitoring will be carried out with the help of current sensors, voltage sensors, frequency sensors and fuel level sensors whose interface displays are via Arduino Nextion Display to monitor whether the generator has worked efficiently, monitor the oil level in the generator and monitor the current, voltage and frequency values ​​in the power supply that currently installed (PLN or Genset). With the Automatic Transfer Switch and Automatic Mains Failure modules, it is hoped that it will make it easier for users to change the power supply source, monitor the power supply source and monitor the generator’s fuel.